Alternative support materials for titania photocatalyst towards degradation of organic pollutants. (June 2018) - Oblak, Rok; Kete, Marko; Štangar, Urška Lavrenčič; Tasbihi, Minoo
Graphical abstract: Highlights: Various titania/binder sol suspensions were prepared using commercial TiO2 nanoparticles (P25, P90 and PC500). Titania/binder suspension was immobilized on stainless steel mesh (SSM) and fiber glass strips (FGSs). Structure and morphology of immobilized photocatalysts were analyzed. The photocatalytic activity of as-prepared immobilized photocatalysts were tested towards degradation of phenol and Reactive Blue 19. Abstract: Stainless steel mesh and hemmed knitted fiber glass strips were coated with TiO2 sol to study the possibilities of the two materials as alternative supports for TiO2 in photocatalytic wastewater treatment process. Commercially available P25, P90 and PC500 powder catalysts were successfully immobilized on stainless steel mesh and fiber glass strips. The prepared photocatalysts were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The retention (stability) of as-prepared layers of photocatalyst on fiber glass strips was tested by sonication test. Best adhesion levels were achieved with P90; with only 17% of photocatalyst loss during the harsh sonication test. The photocatalytic activity was tested with degradation of phenol and commercial textile dye Reactive Blue 19 in flow-through photoreactor. After 240 min of irradiation, mineralization degree of pollutants ranged from 72 to 99% for RB-19 and 38 to 94% for phenol.